1997
DOI: 10.1002/(sici)1097-4636(19970915)36:4<469::aid-jbm4>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Fiber‐matrix interface studies on bioabsorbable composite materials for internal fixation of bone fractures. I. Raw material evaluation and measurement of fiber—matrix interfacial adhesion

Abstract: Abstract:The objective of this study was to characterize strength (IFSS) of C/PLLA and CaP/PLLA microcomposites and evaluate the performance of various fiber-matrix comwas 33.9 and 12.6 MPa, respectively. Upon in vitro hydrolysis, posite systems by studying the mechanical, thermal, and C/PLLA retained 49% of IFSS after 15 days and CaP/PLLA physical properties of the fiber and matrix components, and retained 46% of IFSS after 6 h. Using a fiber fragmentation by studying the fiber-matrix interface adhesion stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…5). All of the scaffolds showed excellent mechanical properties similar to or exceeding cartilage (0.75-1 MPa) and subchondral bone (30-50 Mpa) [32][33][34][35][36] in human osteochondral tissue. Under compressive loading, the bi-phasic key models with both small and large features have the highest modulus when compared with the homogeneous controls and the bi-phasic models, with increases of 27% and 19% (control and biphasic models) among the large pore scaffolds, and with increases of 20% and 64% among the small pore models.…”
Section: Statisticssupporting
confidence: 93%
“…5). All of the scaffolds showed excellent mechanical properties similar to or exceeding cartilage (0.75-1 MPa) and subchondral bone (30-50 Mpa) [32][33][34][35][36] in human osteochondral tissue. Under compressive loading, the bi-phasic key models with both small and large features have the highest modulus when compared with the homogeneous controls and the bi-phasic models, with increases of 27% and 19% (control and biphasic models) among the large pore scaffolds, and with increases of 20% and 64% among the small pore models.…”
Section: Statisticssupporting
confidence: 93%
“…This is well supported by the pH profiles as they indicated significant fibre degradation occurred from day 11 to day 15. The degradation profile of PLLA composites with different types of fibres within PBS were studied by Slivka et al [24]. They reported that an increasing interfacial gap was seen during 30 days of immersion using a laser confocal microscope, which confirmed that interface degradation had occurred during the study.…”
Section: Discussionmentioning
confidence: 92%
“…The fibres within the composite samples were exposed at the edges and hence the fibre/matrix interfaces were directly exposed to the aqueous environment during immersion, where wicking effects could occur and are known to be responsible for the increase of media uptake in the composites [24]. It was also seen that the amount of media absorbed by composites increased with higher Vf, which was as ascribed to the increase in the amount of interfacial area with increasing Vf.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanical properties obtained for the phosphate glass fibers investigated in this study were comparable to properties from a study previously conducted, which also reported on values from the literature. 17 Slivka et al 18 also investigated the mechanical properties for a quaternary PBG fiber containing Fe 2 O 3 and properties quoted for strength were 513 MPa, with a modulus of 42 GPa. The values obtained for the fibers investigated in this study correlated well with those mentioned above.…”
Section: Discussionmentioning
confidence: 99%